SMU is one of seven universities in Asia with the prestigious AACSB Accreditation for its business and accountancy programmes - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
The Singapore Management University’s (SMU) Lee Kong Chian School of Business (LKCSB) and School of Accountancy (SoA) have both earned re-accreditation from AACSB International (AACSB), the largest business education network and longest serving global accrediting body for business schools.